A revision of the simplex species group of the cleptoparasitic bee genus Triepeolus Robertson, 1901 (Hymenoptera: Apidae) - Onuferko, Thomas M.; Rightmyer, Molly G. (European Journal of Taxonomy, 2024)
Species of the cleptoparasitic bee genus Triepeolus Robertson, 1901 (Hymenoptera: Apidae: Nomadinae) of which the female has a trapezoidal or triangular pseudopygidial area with bright, reflective setae and a concave apical margin are revised. This entirely New World group includes the widely known species T. simplex Robertson, 1903 and is thus termed the simplex species group. A total of 18 species in the T. simplex group are recognized as valid, of which seven are newly named and described—T. apache sp. nov., T. eumeniformis sp. nov., T. hirsutus sp. nov., T. oblongimacula sp. nov., T. parahirsutus sp. nov., T. paucipunctatus sp. nov., and T. shoshone sp. nov., all from North America. Eleven redundant names are newly synonymized under three valid ones as follows: Epeolus rugulosus Cockerell, 1917 syn. nov., E. metatarsalis Friese, 1921 syn. nov., and T. bilunatus Cockerell, 1949 syn. nov. under Triepeolus mexicanus (Cresson, 1878); E. lectiformis Cockerell, 1925 syn. nov., T. lusor Cockerell, 1925 syn. nov., and T. junctus Mitchell, 1962 syn. nov. under T. rhododontus Cockerell, 1921; and E. permixtus Cockerell, 1923 syn. nov., T. brunnescens Cockerell & Sandhouse, 1924 syn. nov., T. pacis Cockerell, 1925 syn. nov., E. sarothrinus Cockerell, 1929 syn. nov., and E. sarothrinus var. confluens Cockerell, 1929 syn. nov. under T. segregatus (Cockerell, 1900). Species limits were established using an integrative systematics approach, namely considering morphological and biogeographic evidence as well as DNA barcode data. Taxon concepts are revised for all species in the T. simplex group, with morphological diagnoses and keys presented to enable their identification. Known information on the ranges and ecology of the treated species is summarized.